Analisis Daya Saing Industri Coffee Shop di Kota Medan - Naila Iman; Ani Murwani Muhar; Ade Indah Sari (Jurnal Akutansi Manajemen Ekonomi Kewirausahaan (JAMEK), 2022)
Life in today's urban communities most of them follow trends and have proper channels in tolerating all that comes from outside. Adolescence, as the period of preparing mental self-portraits begins to occur, turns into a significant period for individual development before entering adulthood. Now, children later, this study uses a descriptive type of research with a qualitative approach. This research was conducted at 10 Coffee Shops in the city of Medan. The research was conducted in the period December 2021 – February 2022. The resource persons in this study were the owners/managers of a Coffee Shop in the city of Medan. Data collection techniques are observation, interview, literature study. The types of data sources are primary and secondary data. using the SWOT analysis technique Focus on developing a Coffee Shop business according to the visible trend is a strategy that prioritizes the wishes of consumers in the community, currently the trend is influencing consumers in choosing a food or drink they want to consume, due to lifestyle factors and references from friends. This strategy allows for more precise targeting of the entire consumer in order to create a product that can be seen and accepted by the public. Based on the results of interviews conducted by the author, the strategies adopted by 10 Coffee Shops are different, ranging from promotion on social media, building relationships with customers, improving quality and giving privileges to customers.